Intimate partner violence in sadomasochistic relationships. Issue 1 (2nd January 2016) - Pitagora, Dulcinea
ABSTRACT: Abusive relationships disguised as consensually sadomasochistic (D/s) relationships are a specific type of intimate partner violence (IPV), characterized by a lack of pleasure and the presence of enduring, permeating fear or discomfort on the part of the abused partner that is not confined to a consensual sexual encounter, and do not always occur in the direction of dominant to submissive or male to female partner. Though no research to date has been conducted on IPV in D/s relationships, a review of the literature on IPV in mainstream and sexual minority communities reveals salient commonalities related to the BDSM community. Additionally, there is often an intersectionality of stigmatization that can exponentially affect BDSM-oriented individuals who experience IPV. When consensual BDSM behaviours are conflated with IPV, it can be difficult for someone experiencing abuse within the context of a D/s relationship to seek and receive support from family, peers, health care providers, law enforcement, and society at large.